A Large‐Bandgap Guest Material Enabling Improved Efficiency and Reduced Energy Loss for Ternary Polymer Solar Cells. Issue 5 (8th April 2021) - Yang, Hang; Dong, Yingying; Fan, Hongyu; Wu, Yue; Cui, Chaohua; Li, Yongfang
Abstract : The rational design of guest photovoltaic materials (the third components) for enhancing the power conversion efficiency (PCE) of ternary polymer solar cells (PSCs) is a challenge. In this work, a large‐bandgap material ((5 Z, 5′ Z )‐5, 5′‐(((4, 4, 9, 9‐tetrakis(4‐hexylphenyl)‐4, 9‐dihydro‐ s ‐indaceno[1, 2‐b:5, 6‐b′]dithiophene‐2, 7‐diyl)bis(2, 5‐difluoro‐4, 1‐phenylene))bis(methanylylidene))bis(3‐ethyl‐2‐thioxothiazolidin‐4‐one, IBR‐F) is designed, synthesized, and used as the guest material for ternary PSCs to improve the PCE and reduce the energy loss. IBR‐F possesses a larger energy bandgap of 2.04 eV and a deeper highest occupied molecular orbital (HOMO) level compared to PM6, as well as exhibiting good miscibility with PM6. Thus, the HOMO level is effectively downshifted when blending PM6 with IBR‐F, which is in favor of obtaining a higher open‐circuit voltage ( V oc ). Meanwhile, the incorporation of IBR‐F into the PM6:Y6 blend can maintain the well‐developed bulk‐heterojunction morphological properties of the host blend without extra thermal annealing and improve the charge dissociation and collection efficiencies. As a result, the ternary PSC based on PM6:IBR‐F:Y6 (1:0.2:1.2 w/w) demonstrates a higher V oc of 0.887 V and a reduced energy loss of 0.55 eV compared to the binary device based on PM6:Y6 (1:1.2 w/w) with a V oc of 0.840 V and energy loss of 0.59 eV, delivering an improved PCE of 17.15%. Abstract : A wide‐bandgap guest material is designed, synthesized, and used as the guest material for ternary polymer solar cells to improve the power conversion efficiency and reduce the energy loss.